SOSIALISASI UMKM GO DIGITAL DI DESA CIMAUNG KABUPATEN SERANG - Kurniati Rahmadani; Popi Dayurni (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic has had a significant impact on Micro, Small and Medium Enterprises (UMKM), so social media and digital marketing are one of the solutions in promoting and marketing products. Unfortunately, there are still many UMKM that do not yet have these skills. This service activity aims to help Micro, Small and Medium Enterprises (UMKM) in Cimaung village to be able to adapt to the rapid development of technology through UMKM Go Digital . This community service project focuses on socializing UMKM by utilizing information technology and conducting marketing through social media and e-commerce. So that the digitization of UMKM is one of the important keys so that UMKM can survive and expand business and market scale